Female genital cutting: current practices and beliefs in western Africa. - Sipsma, Heather L; Chen, Peggy G; Ofori-Atta, Angela; Ilozumba, Ukwuoma O; Karfo, Kapouné; Bradley, Elizabeth H (Bulletin of the World Health Organization, 2012)
To conduct a cross-national comparative study of the prevalence and correlates of female genital cutting (FGC) practices and beliefs in western Africa.
Keywords: Adolescent; Adult; Africa, Western; Circumcision, Female; Cross-Sectional Studies; Culture; Female; Health Knowledge, Attitudes, Practice; Health Surveys; Humans; Internationality; Logistic Models; Middle Aged; Prejudice; Prevalence; Self Report; Socioeconomic Factors; Women's Health; Young Adult